2017
DOI: 10.1177/0020764017709484
|View full text |Cite
|
Sign up to set email alerts
|

Stigma experienced by caregivers of patients with severe mental disorders: A nationwide multicentric study

Abstract: This study suggests that caregivers of patients with schizophrenia experience higher stigma than the caregivers of patients with bipolar disorder and recurrent depressive disorder. Higher stigma is associated with higher psychological morbidity in the caregivers. Therefore, the clinicians managing patients with severe mental disorders must focus on stigma and psychological distress among the caregivers and plan intervention strategies to reduce stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
(50 reference statements)
5
33
1
1
Order By: Relevance
“…A total score is generated by summing across 22 items (e.g., 'I feel helpless for having a family member with developmental disability, 'I avoid communicating with a family member having developmental disability') with higher scores reflecting greater affiliate stigma. The ASS showed 7 good internal consistency (α = .98) in other recent studies (Grover et al, 2017); this was also the case here (α = .93).…”
Section: Affiliate Stigmasupporting
confidence: 89%
See 2 more Smart Citations
“…A total score is generated by summing across 22 items (e.g., 'I feel helpless for having a family member with developmental disability, 'I avoid communicating with a family member having developmental disability') with higher scores reflecting greater affiliate stigma. The ASS showed 7 good internal consistency (α = .98) in other recent studies (Grover et al, 2017); this was also the case here (α = .93).…”
Section: Affiliate Stigmasupporting
confidence: 89%
“…Selection of predictor variables was informed by studies involving other caregiving populations that also explored how affiliate stigma might be differentially affected by caregivers' characteristics and family factors (Grover et al, 2017;Koshorke et al, 2017;Singh et al, 2016;).…”
Section: Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another survey in New York, ~43% of the investigated caregivers of people with mental illness expressed a belief that most people devalued their families (Struening et al ). According to previous studies, stigma is consistently associated with higher psychological distress among the caregivers of people with severe mental illnesses (Grover et al, ; Perlick et al, ). In the present review, psychological distress and burden were also apparent among family members.…”
Section: Discussionmentioning
confidence: 92%
“…Surveys have shown that family members (including parents, siblings, spouses, and children) of people with severe mental illness report significant experiences of courtesy stigma. A certain number of family members reported they were stigmatized by the public, and prejudice, blame, avoidance, rejection, and discrimination were directed towards them (Angermeyer et al 2003;Corrigan & Miller 2004;Dinos et al 2004;Grover et al, 2017;Perlick et al, 2007;Phelan et al 1998;Struening et al 2001). Stigma experienced by family members leads to an array of negative consequences, including withdrawal from social relationships, low self-esteem, reduced quality of life, long-term stress and burden, and so on (Allerby et al, 2015;Angermeyer et al 2003;O'Grady 2004;Perlick et al, 2007;Zhang et al, 2018).…”
Section: Introduction and Aimsmentioning
confidence: 99%